2013
DOI: 10.1590/s0004-28032013000200029
|View full text |Cite
|
Sign up to set email alerts
|

Early Functional Results of Biofeedback and Its Impact on Quality of Life of Patients With Anal Incontinence

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…In a clinical trial carried out in 2010 on 26 patients, it was found that biofeedback better improves bowel symptoms and anorectal function compared to standard therapies such as diet, exercise, and laxatives in patients with dyssynergic constipation (Rao, Valestin, Brown, Zimmerman, & Schulze, 2010). In another study on 52 patients with fecal incontinence, biofeedback had positive results in improving patients' symptoms and quality of life (Leite & Lacerda-Filho, 2013). Also, Ahadi et al have concluded that patients with dyssynergic constipation with and without IBS will likely benefit from pelvic floor biofeedback (Ahadi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical trial carried out in 2010 on 26 patients, it was found that biofeedback better improves bowel symptoms and anorectal function compared to standard therapies such as diet, exercise, and laxatives in patients with dyssynergic constipation (Rao, Valestin, Brown, Zimmerman, & Schulze, 2010). In another study on 52 patients with fecal incontinence, biofeedback had positive results in improving patients' symptoms and quality of life (Leite & Lacerda-Filho, 2013). Also, Ahadi et al have concluded that patients with dyssynergic constipation with and without IBS will likely benefit from pelvic floor biofeedback (Ahadi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noticing that wavelet packet decomposition provides numerous effective signal decomposition forms. As shown in Figure 6, an effective signal decomposed form consists of W 1 0 ∩ W 1 1 , W 2 0 ∩ W 2 1 ∩ W 1 1 , W 2 0 ∩ W 2 1 ∩ W 2 2 ∩ W 2 3 , etc. Assume that G = { G 1 , i = 1,2,3,…} is the set of all the effective decomposed forms.…”
Section: System Overviewmentioning
confidence: 99%
“…The value in each subspace is the DB index value of the subspace. The colored subspace is the optimal wavelet packet basis based on DB index, that is W 2 0 , W 3 2 , W 3 3 , W 3 4 , W 3 5 and W 2 3 . Based on the subspaces corresponding to the selected optimal wavelet packet basis, the MEA j, p and P j, p which are not belong to the subspaces from feature vector M and N are removed.…”
Section: System Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Instrumented anorectal biofeedback (BF) is an important component of the management algorithm and improves symptoms and quality of life in both patients with faecal incontinence and patients with defecation disorder-associated constipation. 4,5 Other options for management, such as surgery or sacral nerve stimulation for FI, are much more expensive, invasive and have significantly higher complication rates.…”
Section: Introductionmentioning
confidence: 99%